Antibiotic treatment patterns, costs, and resource utilization among patients with community acquired pneumonia: a US cohort study. Issue 1 (1st January 2017) - Llop, Christopher J; Tuttle, Edward; Tillotson, Glenn S; LaPlante, Kerry; File, Thomas M
ABSTRACT: Objectives : The current treatment options for patients with community-acquired pneumonia (CAP) often present a trade-off between the potential for treatment failure and safety concerns. We set out to investigate real-world outcomes associated with the use of currently available antimicrobial treatment options for CAP in both the outpatient and inpatient (non-intensive care unit [ICU]) settings. Methods : This claims-based retrospective study included adult patients diagnosed with CAP and treated with antibiotic therapies, including any oral fluoroquinolone, macrolide, or beta-lactam monotherapy in the outpatient setting, and intravenous (IV) levofloxacin or IV azithromycin/ceftriaxone in the inpatient setting. Generalized linear model (GLM) regression was used to determine total charges for inpatient stay, the length of stay, and days of inpatient therapy. For outpatients, rates of adverse events (AEs), treatment failure, and hospitalization were compared by type of initial antibiotic therapy using logistic regression multivariate models that controlled for baseline characteristics. Results : A total of 441, 820 outpatients and 33, 287 inpatients treated for CAP between 2007 and 2012 were included in this analysis. In the outpatient setting, fluoroquinolone therapy led to a higher rate of documented AEs (adjusted odds ratio [OR]: 1.23; 95% confidence interval [CI]: 1.20–1.25; p < 0.0001) but a lower rate of retreatment (adjusted OR: 0.9; 95% CI: 0.87–0.94; p < 0.0001) compared with macrolides. Both AEs and retreatment in these patients were associated with increased costs. For patients treated with the IV macrolide/beta-lactam combination compared with IV fluoroquinolone in the inpatient setting, a significantly longer length of stay in hospital (4.71 vs. 4.38 days; p < 0.0001) and greater overall costs (3, 535 more per stay; p < 0.0001) were observed. Conclusion : In both the inpatient and outpatient settings, the development of additional efficacious treatment options that have a reduced AE burden for patients with CAP may be warranted.